Manajemen Syariah: Sebuah Pemikiran, ‎Wacana dan Realita (Bagian Pertama)‎ - Ismail Nawawi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2010)
This article is aimed at portraying the thought, discourse of economic management from islamc perspective, especially in the aspects of business life, economy, and social interaction which are bound to islamic values as a reflection of living Islam totally (kaffah). This is important because all human actions are to be held responsible before God Almighty hereafter. Basically, shariah based management is founded upon three aspects; management, ethics, and spiritiality in which this three aspect interact each other inseparably. Therefore, Al-Qur’an and al-Hadith as the source of value in Islam become instrumental in implementing managrial steps to achieve rational, efefective and eficient goals. The interisting aspect of this thought is that shariah-based management is with the two truths. Thefirst is empirical truth which is prooved by transparent and clear implementation and transcendental truth which revolves around the thought and understanding that honesty, fairness, and honour have impact on the harmonious, peaceful, stable, and tolerant life in the bound of cooperation.